Idiopathic intracranial hypertension as a cause of severe intractable headache in a patient with Systemic Lupus Erythematosus: A case report from Eastern Nepal - Shah, Bhupendra; Amprayil, Mathew Ibrahim; Taparia, Rahul; Pokhrel, Shailesh Mani (Journal of Advances in Internal Medicine, 2018)
Correction: Unfortunately, several authors on this paper were omitted. Therefore, on 15th April 2019 the following authors were added to the paper: Mathew Ibrahim Amprayil, Rahul Taparia and Shailesh Mani Pokhrel. The editorial board apologises for this error. The common risk factors for Idiopathic intracranial hypertension are obesity, female gender, hypervitaminosis A, and steroid withdrawal. Even though Idiopathic intracranial hypertension is considered as a neuropsychiatric manifestation of Systemic lupus erythematosus, it is often missed by the physician as a cause of a headache in a patient with Systemic lupus erythematosus. We report a case of 21-year-old female who presented in our outpatient department with a history of a severe intractable progressive headache for a duration of four weeks and blurring of vision for five days who was later diagnosed as a case of idiopathic intracranial hypertension with Systemic lupus erythematosus. She recovered dramatically with the institution of steroid and acetazolamide therapy.